Reforming Business Taxes : What is the Effect on Private Sector Development? - Bruhn, Miriam (World Bank, Washington, DC, 2012)
Tax rates and the administrative costs of tax compliance are key concerns of business. Studies within and across countries suggest that lowering corporate tax rates can increase investment, reduce tax evasion by formal firms, promote the creation of formal firms, and ultimately raise sales and Gross Domestic Product (GDP). These benefits, however, need to be balanced against other objectives of the tax regime. Although less is known about the effects of reducing compliance costs, evidence suggests that this too can lead to more formal firms and higher sales.